Role of Volume Replacement during Neonatal Resuscitation in the Delivery Room - Deepika Sankaran; Emily C. A. Lane; Rebecca Valdez; Amy L. Lesneski; Satyan Lakshminrusimha (MDPI AG, 2022)
Volume expanders are indicated in the delivery room when an asphyxiated neonate is not responding to the steps of neonatal resuscitation and has signs of shock or a history of acute blood loss. Fetal blood loss (e.g., feto-maternal hemorrhage) may contribute to perinatal asphyxia. Cord compression or a tight nuchal cord can selectively occlude a thin-walled umbilical vein, resulting in feto-placental transfusion and neonatal hypovolemia. For severe bradycardia or cardiac arrest secondary to fetal blood loss, Neonatal Resuscitation Program (NRP) recommends intravenous volume expanders (crystalloids such as normal saline or packed red blood cells) infused over 5 to 10 min. Failure to recognize hypovolemia and subsequent delay in volume replacement may result in unsuccessful resuscitation due to lack of adequate cardiac preload. However, excess volume load in the presence of myocardial dysfunction from hypoxic-ischemic injury may precipitate pulmonary edema and intraventricular hemorrhage (especially in preterm infants). Emergent circumstances and ethical concerns preclude the performance of prospective clinical studies evaluating volume replacement during neonatal resuscitation. Translational studies, observational data from registries and clinical trials are needed to investigate and understand the role of volume replacement in the delivery room in term and preterm neonates. This article is a narrative review of the causes and consequences of acute fetal blood loss and available evidence on volume replacement during neonatal resuscitation of asphyxiated neonates.